2022
DOI: 10.3389/fmars.2022.811284
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Environmental Survival of Marteilia refringens, a Marine Protozoan Parasite of the Flat Oyster Ostrea edulis, Through an Environmental DNA and Microscopy-Based Approach

Abstract: Outside-host parasite survival is a key parameter to better understand disease mechanisms, especially for marine pathogens transmitted from one host to another through an environmental stage. For non-cultivable micro-parasites like Marteilia refringens, a protozoan parasite infecting the flat oyster Ostrea edulis, investigating this parameter requires innovative approaches. In the present study, we have developed an Environmental DNA (eDNA)-based method allowing detecting and quantifying up to 25 and 10 parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…This Taqman assay was optimized in order to detect parasite DNA (and RNA for B. ostreae) in environmental samples. These eDNA-based approaches are very promising as they avoid killing oysters, which is important in the context of zone status evaluation, surveillance and restoration programs (Mérou et al, 2020;Mérou, 2021;Mérou et al, 2022).…”
Section: Diagnosis Microscopy and Molecular Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…This Taqman assay was optimized in order to detect parasite DNA (and RNA for B. ostreae) in environmental samples. These eDNA-based approaches are very promising as they avoid killing oysters, which is important in the context of zone status evaluation, surveillance and restoration programs (Mérou et al, 2020;Mérou, 2021;Mérou et al, 2022).…”
Section: Diagnosis Microscopy and Molecular Toolsmentioning
confidence: 99%
“…Juveniles and older life stages are known to be susceptible (Grizel, 1985). Recently, an eDNA-based approach allowed parasite DNA to be detected in seawater 20 days after release from the flat oysters (Mérou et al, 2022).…”
Section: Host-parasite Interactions and Life Cycles Of Parasitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the infection from Ostrea edulis and Mytilus galloprovincialis to the copepod has been successfully demonstrated ( Audemard et al., 2002 ; Carrasco et al., 2008 ), the transmission from the copepod to flat oysters or mussels has not been proved yet, leaving its role into the parasite life-cycle unclear. M. refringens enters bivalves through feeding process and then develops in the digestive epithelia by endogenous divisions before being eliminated with faeces as sporangia containing mature spores ( Grizel et al., 1974 ; Perkins, 1976 ; Audemard, 2001 ; Mérou et al., 2022 ). In flat oysters, M. refringens detection frequency peak occurs in summer (between June to September) whereas the parasite is usually absent or found in low numbers in winter and early spring ( Audemard et al., 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, M. refringens detection frequency showed two peaks in summer and spring ( Carrasco et al., 2007 ; Boyer et al., 2013 ; Arzul et al., 2014 ). More recently, an environmental DNA (eDNA) based study revealed that M. refringens DNA could be detected in seawater and flat oysters faeces at least during 20 days after parasites were released from oysters, with a more stable detection over time in faeces, suggesting a better survival of the parasite in this matrix ( Mérou et al., 2022 ). Although it is now suggested to be a different species, M. pararefringens (previously M-type) transmission also seems restricted to the warmest period of the year as suggested by ( Bøgwald et al., 2022 ) in a study carried out on blue mussel Mytilus edulis in a heliothermic marine oyster lagoon in western Norway.…”
Section: Introductionmentioning
confidence: 99%